The Policy of the Youth Sports and Tourism Office in Developing Sports Tourism in East Ogan Komering Ulu Regency - Yogi Indrawan (STKIP Muhammadiyah Kuningan, 2023)
Disporapar Ogan Komering Ulu Timur Regency as implementing policies in the field of Sports Youth and Tourism, aims to develop sports tourism in East Ogan Komering Ulu district. The aim of this research is to find out the policies of Disporapar of Ogan Komering Ulu Timur district in developing sports tourism, the factors that support and hinder policies in developing sports tourism, the response and participation of the community in sports tourism development programs. The method used in this research is using descriptive qualitative. Data collection techniques using observation techniques, interviews, and documentation or data triangulation. The main data sources or research subjects are the Head of East Ogan Komering Ulu District Disporapar, managers of tourist destinations, and the community. Research results: Indicates that the inhibiting factor in the development of sports tourism is the source of funds, because for the maintenance of sports tourism facilities and for holding events at sports tourism destinations, then the supporting factors, namely the completeness and condition of sports tourism facilities and infrastructure, are very good for used for visitors, plus the enthusiasm and interest of the community for sports tourism is very high, thus the need for coordination from various parties to achieve the development of sports tourism. Conclusion: In the development of sports tourism, it is necessary to pay attention to many aspects. One of the important aspects is that the coordination of all parties must go well, so that the desired goals can be achieved in developing sports tourism, and then must pay attention to elements such as funding, management, availability of human resources Human resources, socialization of the implementation of the sports tourism development program, the quality of the facilities and infrastructure used, and community participation so that it can become an attraction for people to go on sports tours.